The temporality of the epidemiological transition in Chile, 1862-2018 - Llorca-Jaña, Manuel; Rivas, Javier; Rivero-Cantillano, Rodrigo (Dynamis, 2023)
This article analyzes the nature and temporality of the epidemiological transition (ET) in Chile, paying special attention to the composition of the causes of death in that country from 1862 to 2018. The evidence provided in this article allows us to establish that the ET effectively occurred in Chile under the “contemporary-late” model, to which we could add the adjective “accelerated”. Our results highlight the recentness of the overcoming of the first phase of Chilean TE in comparison to most developed countries, due to the prominence of infectious diseases as the main cause of death until the middle of the 20th century and the acceleration of this process (the short time period between the 1940s and the 1960s). Overcoming the first phase of ET was mainly possible due to the sudden “importation” of international technological advances (sulfonamides and antibiotics in particular) during a period in which there were still no substantial nutritional improvements in the population or major advances in the supply of drinking water or sewage services.